A Porphyromonas gingivalis Capsule-Conjugate Vaccine Protects From Experimental Oral Bone Loss - Rocha, Fernanda G.; Berges, Aym; Sedra, Angie; Ghods, Shirin; Kapoor, Neeraj; Pill, Lucy; Davey, Mary Ellen; Fairman, Jeff; Gibson, Frank C. (Frontiers in Oral Health, 2021)
Periodontal diseases are chronic inflammatory diseases of the periodontium that result in progressive destruction of the soft and hard tissues supporting the teeth, and it is the most common cause of tooth loss among adults. In the US alone, over 100 million individuals are estimated to have periodontal disease. Subgingival bacteria initiate and sustain inflammation, and although several bacteria have been associated with periodontitis, Porphyromonas gingivalis has emerged as a key etiological organism significantly contributing to the disease. Currently, intensive clinical maintenance strategies are deployed to mitigate further progression of disease in afflicted individuals; however, these treatments often fail to stop disease progression and as such development of an effective vaccine for periodontal disease is highly desirable. We generated a conjugate vaccine comprising of purified capsular polysaccharide of P. gingivalis conjugated to eCRM®, a proprietary and enhanced version of the CRM197 carrier protein with pre-determined conjugation sites (Pg-CV). Mice immunized with alum adjuvanted Pg-CV developed robust serum levels of whole organism-specific IgGs in comparison to animals immunized with unconjugated capsular polysaccharide alone. Using the murine oral bone loss model, we observed that mice immunized with the capsule-conjugate vaccine were significantly protected from the effects of P. gingivalis-elicited oral bone loss. Employing a pre-clinical model of infection-elicited oral bone loss, our data support that a conjugate vaccine incorporating capsular polysaccharide antigen is effective at reducing the main clinical endpoint of periodontal disease – oral bone destruction. Further development of a P. gingivalis capsule-based conjugate vaccine for preventing periodontal diseases is supported.